SISTEM BUS RAPID TRANSIT TRANSJAKARTA DALAM STUDI REKAYASA SOSIAL - Wulan Tangkudung, Ellen Sophie; Modjo, Robiana; Fitriati, Rachma; Aminah, Siti (Jurnal Transportasi, 2011)
Jakarta has developed an integrated transport system and planned, called Macro Transportation System planto address transportation problems in Jakarta. Transjakarta, a Bus Rapid Transit system (BRT), is one of thepublic transportation facilities included in the Macro Transportation System plan, which was intended as aneffort to developa new urban transportation culture. This study used the concept of socio engineering toassess the Transjakarta transport service in Jakarta. The results indicate that the highest service quality relatedto the dimension of empathy and lower service quality associated with the tangible dimension.Keywords: integrated transport system, Bus Rapid Transit, socio engineering.